Oncolytic measles vaccines encoding PD-1 and PD-L1 checkpoint blocking antibodies to increase tumor-specific T cell memory - Veinalde, Rūta; Pidelaserra Martí, Gemma; Moulin, Coline; Jeworowski, Lara M.; Küther, Linda; Buchholz, Christian J.; Jäger, Dirk; Ungerechts, Guy; Engeland, Christine Elisabeth (Molecular therapy. Oncolytics, 2022)
PD-1/PD-L1 checkpoint blockade has achieved unprecedented success in cancer immunotherapy. Nevertheless, many immune-excluded tumors are resistant to therapy. Combination with oncolytic virotherapy may overcome resistance by inducing acute inflammation, immune cell recruitment, and remodeling of the tumor immune environment. Here, we assessed the combination of oncolytic measles vaccine (MV) vectors and PD-1/PD-L1 blockade. In the MC38cea model of measles virus oncolysis, MV combined with anti-PD-1 and MV vectors encoding anti-PD-1 or anti-PD-L1 antibodies achieved modest survival benefits compared with control MV or vectors encoding the antibody constant regions only. Analyses of tumor samples and tumor-draining lymph nodes revealed slight increases in intratumoral T cell effector cytokines as well as a shift toward an effector memory phenotype in the T cell compartment. Importantly, increased IFN-γ recall responses were observed in tumor rechallenge experiments with mice in complete tumor remission after treatment with MV encoding anti-PD-1 or anti-PD-L1 compared with control MV. These results prompted us to generate MV encoding the clinically approved agents pembrolizumab and nivolumab. Previously, we have generated MV encoding atezolizumab. We demonstrated the functionality of the novel vectors in vitro. We envision these vectors as therapeutics that induce and support durable anti-tumor immune memory.
Gesehen am 31.01.2023